Pelabuhan Perikanan Di Pulau Tello: Tinjauan Fungsional Dan Potensi Pengembangan - Telaumbanua, Dewi Masa Leni; Telaumbanua, Betzy Victor (CV. SINAR HOWUHOWU, 2025)
fishing activities, especially in islands with limited accessibility such as Tello Island, South Nias Regency. This study aims to analyze the function, role, and development potential of Tello Island Fishing Port in order to strengthen the local fishing sector. The method used is a literature study with a qualitative descriptive approach through secondary data review and field observation. The results show that this port functions as a fish landing center for local fishermen, but various important facilities such as the Fish Auction Site (TPI), cold storage, and fish processing units are severely damaged and have not been repaired. The available ice storage is also unable to meet the daily needs of fishermen. Based on these findings, it can be concluded that the development of the fishing port on Tello Island is urgently needed through the improvement of post-harvest facilities, increased storage capacity, and the empowerment of the fishing community. It is recommended that the local government and relevant stakeholders immediately revitalize the port infrastructure to support the sustainability of fisheries and improve the economy of coastal communities.